FIBER QUALITIES OF PRETREATED BETUNG BAMBOO (Dendrocalamusasper) BY MIXED CULTURE OF WHITE-ROT FUNGI WITH RESPECT TO ITS USE FOR PULP/PAPER - Widya Fatriasari; Ratih Damayanti; Sita Heris Anita (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2013)
Previous research on anatomical structures of pretreated large (betung) bamboo (Dendrocalamusasper) using single culture of white-rot fungi has been investigated, which revealed that the pretreatment caused the decrease in the Runkel ratioas well as the coefficient rigidity and the increase in the flexibility ratio of their corresponding bamboo fibers. However, there is no study reported on the anatomical structure changes of them caused by pretreatment using mixed culture of white-rot fungi. This paper reports the results of the research on paper/pulp quality after different treatments. Pretreatment that used Trametes versicolor fungi and lasted for 45 days inflicted intensive fiber damages compared with those of untreated bamboo (control). Fresh and barkless large (betung) bamboo chips of 2 year's old, and 1.6 cm in length, were inoculated by 10% of mixed culture of white-rot fungi inoculums stock for 30 and 45 days in room temperature. There were four treatment groups of mixed culture, i.e T. versi color and P. ostreatus (TVPO); P. ostreatus and P. chrysosporium (POPC); P. chrysosporium and T.versi color (PCTV); and P.chrysosporium, T.versicolorand P.ostreatus (TVPCPO).After the inoculation period, the chips weremacerated into separate fibers using Scultze method to analyze the fiber dimension and its derived values. The fibers were then observed regarding their macro and microscopic structures by optical microscope. Mixed culture pretreatment of white-rot fungi accelerated improvement of fiber morphology and fiber derived value characteristics, except for Muhlsteph ratio. The fiber derived values oftreated bamboo tended to improve compared to those of untreated bamboo, there by requiring milder pulping conditions. Accordingly, the treated bamboo would indicatively produce a good quality pulp (grade I) based on FAO and LPHH (Forest Product Research Report) requirements. Co-culture treatment using P. chrysosporium and P. ostreatus for 45 days produced the best fiber dimension and its derived value properties. The fungi hypae colonized on the surface area of bamboo followed by mycelium penetration into substrate (bamboo-inner structure). The partial degradation caused by delignification indicatively attributed to the fungi activity was shown in the macroscopic images.